Nitrate loss from fertilized crop fields: does slope steepness matter? - Jakab, Gergely; Karsai, Gergely; Szalai, Zoltán; Szabó, Judit (JOURNAL OF LANDSCAPE ECOLOGY, 2017)
Nitrogen (N) is one of the most important nutrients that plants and microbiota need. In general, under temperate conditions its availability in soil limits biological production especially on intensively cultivated crop fields. Cultivation gradually mitigates organic carbon and nitrogen content of the soil hence a continuous N supply is of crucial importance for reasonable crop production. Therefore, N fertilization is a necessity that has additional environmental effects. Most of the applied fertilizers contain inorganic N, mainly nitrate, which is soluble in water and, accordingly, mobile in the soil. Nitrate can be delivered from the soil by surface runoff or percolation to the deeper layers and the ground water. Present study aimed to compare nitrate losses triggered by the same precipitation event (40 mm h-1) on different slope steepness (5 and 12%) and soil status (seedbed; sealed and crusted condition) on a Cambisol right after inorganic N fertilizer (100 kg ha-1) application using laboratory rainfall simulation. Results indicated that at each precipitation event, only the first 0.5 mm runoff contained considerable amount of nitrate ( 170 mg L-1), while main loss was due to percolation (also 170 mg L1 but all along the percolation period). Accordingly, slope steepness (and also surface conditions) affects nitrate loss via controlling the volume of infiltrated and percolated water. Namely, the crusted steeper slope had the lowest nitrate loss, because most precipitation water was turned to runoff. Evaporation from the soil surface between the precipitations generated upward moisture movement in the profile that finally triggered a higher nitrate concentration on the surface. This N was supposed to be the reason of the increased nitrate content of initial runoff. Accordingly, nitrate loss is inversely proportional to slope steepness, although the effect is subordinate.